2013
DOI: 10.1186/1471-2261-13-118
|View full text |Cite
|
Sign up to set email alerts
|

Acute coronary syndrome in young Sub-Saharan Africans: A prospective study of 21 cases

Abstract: BackgroundCoronary heart disease remains the leading cause of death in developed countries. In Africa, the disease continues to rise with varying rates of progression in different countries. At present, there is little available work on its juvenile forms. The objective of this work was to study the epidemiological, clinical and evolutionary aspects of acute coronary syndrome in young Sub-Saharan Africans.MethodsThis was a prospective multicenter study done at the different departments of cardiology in Dakar. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 17 publications
1
9
2
Order By: Relevance
“…Another plausible reason could be lack of adequate accessibility and affordability of the medication in relation to the socio-economic status of the patients. Our study revealed a lower percentage of thrombolytic use compared to studies from Kenya 79.5% [30], South Africa 18% [31], sub-Saharan countries 44.4% [32] and Iran 46.3% [33]. This could be due to better availability and accessibility of thrombolytic medications in Kenya, South Africa and similarly in Iran too.…”
Section: Discussioncontrasting
confidence: 60%
“…Another plausible reason could be lack of adequate accessibility and affordability of the medication in relation to the socio-economic status of the patients. Our study revealed a lower percentage of thrombolytic use compared to studies from Kenya 79.5% [30], South Africa 18% [31], sub-Saharan countries 44.4% [32] and Iran 46.3% [33]. This could be due to better availability and accessibility of thrombolytic medications in Kenya, South Africa and similarly in Iran too.…”
Section: Discussioncontrasting
confidence: 60%
“…In some instances, the delay in reaching the hospital may be as long as 6-10 days, including 2 days to reach the first medical facility, with an additional 6 days to reach the cardiology department [14]. The delay before reaching hospital has decreased in large cities, such as Dakar, where it has dropped from 53 hours in 2007 to 37 hours in 2015 [15] and to 14.5 hours among younger patients referred to the Dakar Coronary Care Unit [16]. However, while delays from symptom onset to receipt of therapy have substantially decreased in large urban and suburban areas, such as Dakar or Abidjan, delays exceeding 12 hours remain rather common, precluding, in turn, an effective revascularization attempt in most instances.…”
Section: Time From Symptom Onset To Receipt Of Reperfusion Therapymentioning
confidence: 99%
“…There are many genomic studies suggesting different chromosomal abnormalities contributing to the onset of ACS in young [34]. [40][41][42].…”
Section: Discussionmentioning
confidence: 99%